Management of Tourism Villages with Collaborative Governance in Kebumen District - Prasetyo, Hendrawan (Universitas Medan Area, 2023)
Development in the tourism sector aims to manage natural resources in the region and requires inter-sectoral participation, by both government and society and the private sector in tourism management. The success of tourism development is the development that involves community participation and can provide benefits to local communities in terms of economic, social, and cultural. The involvement of various parties has the potential to advance the region by collaborating on the resources owned by the local government, the community, and the private sector. This study aims to find out how collaboration is carried out by actors in the framework of building a tourism village in Kebumen Regency to develop regional tourism. This study uses exploratory research methods using a qualitative approach. Through this research, an analysis is carried out regarding the development of collaborative governance-based tourism villages in Kebumen Regency. The research location in this study was in Kebumen Regency and the research sites were in six tourist villages in Kebumen Regency. The focus of this research is on issues related to the realization of collaborative governance in the management of tourism villages to develop regional tourism potential in Kebumen Regency. Management of tourism villages requires the involvement of various parties consisting of local government, village government, tourism awareness groups, and the private sector and is carried out optimally.